In the shadows of empires: Early medieval Croatia in the ninth and tenth centuries - Majnarić, Ivan (History compass, 2018)
The early medieval history of the European periphery in the 9th century and its relations with the Carolingian and the Byzantine Empire have in the last two decades become a focal point for medievalists. In a number of research papers studying the areas beyond the eastern borders of the Carolingian Empire, interest has been shown for the northeastern hinterlands of the Adriatic coast, that is, the area in which the Duchy of Croatia was formed during the 9th century. The question at the heart of these medievalists' interest is the appearance of Croats in recorded history. The modern solutions to this question are not unanimous, as they range from a collective migration in the 7th century to the creation of a Croatian elite in the first half of the 10th. Also, due to the lack of primary sources, various methodological templates have been used to make sense of the past, applied chiefly—until recently—by non-Croatian historians. Meanwhile, the developmental perspective of the 9th century has often been disregarded due to the ever-present fragmentation of research—especially regarding the interrelated shaping of social and identity structures during the Carolingian and post-Carolingian era—although this has proven essential as a means of historical inquiry when primary sources are scarce. The formation and survival of structures in early medieval Croatia during the 9th and 10th centuries should be considered in terms of the long-term binarity of identities at the juncture of the Carolingian and the Byzantine Empire, as this paper will attempt to do.